CAUSES AND EFFECTS OF LOWERING THE STANDARD OF LIVING IN UKRAINE - Stativka N.V.; Nadtochii A.O. (Pressing Problems of Public Administration, 2016)
The paper is devoted to challenges of providing decent living standards for the population as the basisfor human potential preservation and development. The main causes of lowering the Ukrainian population’sliving standards, the nature of its trends and eventual threats to the sustainable development of thenational economy have been determined. Proposals for the living standards improvement by means ofstate policy have been substantiated.